The combined monitoring of brain stem auditory evoked potentials and intracranial pressure in coma. A study of 57 patients. Issue 9 (September 1992) - García-Larrea, L; Artru, F; Bertrand, O; Pernier, J; Mauguière, F
Abstract : Continuous monitoring of brainstem auditory evoked potentials (BAEPs) was carried out in 57 comatose patients for periods ranging from 5 hours to 13 days. In 53 cases intracranial pressure (ICP) was also simultaneously monitored. The study of relative changes of evoked potentials over time proved more relevant to prognosis than the mere consideration of "statistical normality" of waveforms; thus progressive degradation of the BAEPs was associated with a bad outcome even if the responses remained within normal limits. Contrary to previous reports, a normal BAEP obtained during the second week of coma did not necessarily indicate a good vital outcome; it could, however, do so in cases with a low probability of secondary insults. The simultaneous study of BAEPs and ICP showed that apparently significant (greater than 40 mm Hg) acute rises in ICP were not always followed by BAEP changes. The stability of BAEP's despite "significant" ICP rises was associated in our patients with a high probability of survival, while prolongation of central latency of BAEPs in response to ICP modifications was almost invariably followed by brain death. Continuous monitoring of brainstem responses provided a useful physiological counterpart to physical parameters such as ICP. Serial recording of cortical EPs should be added to BAEP monitoring to permit the early detection of rostrocaudal deterioration.